Answer:
y - 6 = -4(x+1) is equivalent to equation C: y = -4x + 2
Step-by-step explanation:
Solve the given y - 6 = -4(x+1) for y and remove the parentheses shown:
y - 6 = -4(x+1) becomes
y = -4(x + 1) + 6, or
y = -4x - 4 + 6, or
y = -4x + 2 This is equivalent to equation C.
Answer:
$9.50
Step-by-step explanation:
$123.50/13 ladies
they each pay $9.50
Answer:no
Step-by-step explanation:
it’s equal to -10 + 10h by the commutativity of addition and subtraction
Pretty sure it’s “b= p/2 - a” which is the second answer
The answer is 21 because 189 divided by 9 is 21